Dynamics of Resistance to The Poetry “A Jacket Stained with Blood” by Taufiq Ismail - Gracesela Septiana Sibuea; Rosmawaty Harahap (Journal of Aceh Studies, 2026)
This article analyzes the dynamics of resistance to the 66th generation through the poem "A Jacket Stained with Blood" by Taufiq Ismail. This poem highlights the struggle and sacrifice of warriors in protecting the homeland from enemy threats, as well as the importance of maintaining national identity and heritage. This article explores how the poem "A jacket stained with blood" reflects the deep spirit of struggle for the homeland, as well as respect for the struggle and sacrifice of fighters in protecting and defending their homeland. This article uses library research or library research methods. By utilizing library searches. Library research is not just reading literature or reading the books needed to write articles. This poem is an example of a work that explores historical events to convey a message about the importance of freedom and justice for the nation.